EFFECTIVENESS OF PROBLEM BASED LEARNING MODEL (PBL) SETTING OPEN ENDED APPROACH IN MATHEMATICS LEARNING - Muhammad Nur Sabar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2017)
The study aims at examining (1) the effectiveness of the implementation of Problem Based Learning (PBL) model using Open Ended approach, (2) the students’ learning result in mathematics who were taught by using PBL model with Open Ended approach, (3) the students’ activities in teaching and learning process by using PBL model with Open Ended approach, and (4) the students’ response on learning. The study is pre-experiment research with One Group Pretest-Posttest Design. The populations of the study were class VIII students at SMPN 33 Makassar of academic year 2016/2017 wich consisted of 10 classes. Samples were selected by employing Cluster Random Sampling technique and obtained class VIIIE as the research sample. Data were obtained by using learning result test instrument, observation sheet of students’ activities, observation sheet of learning implementation, and questionnaire of students’ response. The results of the study reveal that the learning result score of class VIII students in mathematics I sin high category, the mean 83.22, and deviation standar 8.549, the classical completeness is 87.50%, the mean of normalized gain is in high category, the students’ activity is in very active category, and students’ response on the implementation of PBL model with Open Ended approach is positive. The result of hypothesis test indicates that PBL model with Open Ended approach is effective to implemented in Mathematics learning to class VIII students at SMPN 33 Makassar.